The Effect of Skipping Training on Straight Kick Speed in Pencak Silat at State Senior High School 1 Katapang - Nurjanah Jayanti; Agus Rusdiana; Iman Imanudin (Journal of Physical Education Health and Sport, 2025)
This study aims to determine the effect of skipping training on straight kick speed in pencak silat. The method used is a quasi-experimental with a pretest-posttest control group design. The research subjects consisted of 10 extracurricular pencak silat athletes at Senior High School 1 Katapang who were divided into two groups, namely the experimental group and the control group. The experimental group was given treatment in the form of skipping training for 3 weeks with a frequency of 4 times a week. The instrument used was a straight kick speed test in 10 seconds. The results of the paired sample t-test showed that there was a significant increase in the experimental group (p < 0.05), with an average increase of 6.2 kicks. While in the control group, no significant increase was found. The independent sample t-test also showed a significant difference between the experimental and control groups (p < 0.05). Thus, skipping training is proven to be effective in increasing straight kick speed in pencak silat athletes. The results of this study can be used as a reference by coaches in developing training programs aimed at improving athlete performance.